Decompression Mechanism of Radish Seed in Prehypertension Rats through Integration of Transcriptomics and Metabolomics Methods. (31st January 2023) - Jia, Qiang; Qi, Yuchen; Li, Hanbo; Ding, Hai; Qi, Dongmei; Li, Yunlun
Abstract : Radish seed (RS), the dried ripe seed of Raphanus sativus L., is widely used in traditional Chinese medicine (TCM) to reduce blood pressure. However, the molecular and pharmacological mechanisms underlying its therapeutic effects are still unclear. In this study, we analyzed the effects of RS in a rat model of prehypertension and assessed the mechanistic basis by integrating transcriptomics and metabolomics. RS administration significantly reduced blood pressure in prehypertensive male Wistar rats, negatively regulated endothelin-1, increased nitric oxide levels, and reduced the exfoliation of endothelium cells. In vitro vascular ring experiments further confirmed the effects of RS on vascular endothelial cells. Furthermore, we identified 65 differentially expressed genes (DEGs; P a d j < 0.05 and fold change (FC) > 2) and 52 metabolites (VIP > 1, P < 0.05 and FC ≥ 2 or ≤0.5) in the RS intervention group using RNA-seq and UPLC-MS/MS, respectively. A network of the DEGs and the metabolites was constructed, q which indicated that RS regulates purine metabolism, linoleic acid metabolism, arachidonic acid metabolism, circadian rhythm, and phosphatidylinositol signaling pathway, and its target genes are Pik3c2a, Hspa8, Dnaja1, Arntl, Ugt1a1, Dbp, Rasd1, and Aldh1a3. Thus, the antihypertensive effects of RS can be attributed to its ability to improve vascular endothelial dysfunction by targeting multiple genes and pathways. Our findings provide new insights into the pathological mechanisms underlying prehypertension, along with novel targets for the prevention and treatment of hypertension.